DAKWAH DIGITAL DARI GEN Z UNTUK GEN Z (GERAKAN DAKWAH MEDIA PESANTREN) - Hasyim Iskandar (JDARISCOMB:Jurnal Komunikasi dan Penyiaran Islam, 2023)
Da'wah is currently mostly done through digital media. The development of information technology and science brings innovation to the spread of da'wah. The development of digital media coincides with the emergence of a new generation known as Generation Z. They are not only objects of da'wah or mad'u, but the role of da'I is also carried out by their own generation through digital technology. namely social media. This paper uses a writing method through a descriptive approach. This research is intended to analyze and describe how the da'wah movement through digital media in reaching generation Z people is carried out from generation Z itself, based on literature analysis.